The Identity of Religious Pedagogy - Zbigniew Marek (Nicolaus Copernicus University in Toruń, 2014)
The article contributes to the discussion on the nature of religious pedagogy and its scope of the study. It has been recognized as a pedagogical "option" or "trend", which takes into account research on the educational situation respecting the religious dimension of comprehensively considered life issues both of a pupil and a researcher. This area of research interest of religious pedagogy indicates that it leads to creation of a theory of teaching and educational process based on religious content. In this sense, religious pedagogy includes "educational potential of various forms of religion and formulates a theory of religious education and religious socialization in the Church, family, school and society" and becomes an independent scientific discipline. This significantly distinguishes it from catechetics, which belongs to the theological sciences. Religious pedagogy uses methodology in its research, both of theological sciences and of the humanities. While the nature of religious pedagogy is still being debated, we can already state that this discipline reveals new perspectives for exploration of meaning of all being in the world. This endeavor should be supported by enhancing in the educational processes the role of religious knowledge, which can transform man's way of thinking. This in turn calls for an absolute respect for God, not only as a being on whom a man is dependent, but also for the recognition of the fact that God never lies.